Otimização geométrica de hidrociclones com cilindros e cones permeáveis - Salvador, Fernanda Falqueto (2017)
Hydrocyclones are versatile equipments used in several industrial processes, which use the centrifugal separation principle to remove or classify solid particles in a fluid, based on particle size, shape and density. Each application has its own particular requirements and interferes both in the design and in the operating conditions. Therefore, appropriately choosing the equipment dimensions depends on the main objective of the process. In addition, it is possible to enhance the performance of the hydrocyclones by the simultaneous use of new unit operations with a hydrocyclone, such as filtration. The filtering hydrocyclone, which is part of the category of unconventional equipment, was developed by researchers of FEQUI/UFU in order to improve separation efficiency or reduce energy costs. In this thesis, the effect of the incorporation of the porous cylinder and cone, together or separately, on the conventional hydrocyclone was studied experimentally. Thus, the central composite design was proposed for each of the four modalities studied (HCICOF, HCIF, HCOF and HCON) considering the main dimensions of a hydrocyclone. An optimization was performed from the experimental data of the CCD, where three new geometries were obtained for each modality through the response surface methodology combined with the use of the Differential Evolution algorithm. The objective of the optimization was to find three categories of hydrocyclone: case 1 - maximum separation efficiency; Case 2 - minimum underflow-to- throughput ratio; Case 3 - minimum Euler number. The experimental results were satisfactory to validate the optimization techniques showing that the optimized geometries reached higher total efficiencies (HCICOF-OT1: n=89.59%; HCIF-OT1: n=91.91%; HCOF-OT1: n=90.31%; HCON-OT1: n=95.47%), lower underflow-to-throughput ratio (HCICOF-OT2: RL=12.41%; HCIF-OT2: RL=7.89%; HCOF-OT2: RL=9.59%; HCON-OT2: RL=5.53%) and lower Euler numbers (HCICOF-OT3: Eu=582; HCIF-OT3: Eu=665; HCOF-OT3: Eu=648; HCON-OT3: Eu=845) than those obtained for the 25 configurations of the central composite design.